Left ventricular morphology and function in adolescents: Relations to fitness and fatness - Dias, K.; Spence, Angela; Sarma, S.; Oxborough, D.; Timilsina, A.; Davies, P.; Cain, P.; Leong, G.; Ingul, C.; Coombes, J. (Elsevier Ireland Ltd., 2017)
© 2017 Background Obesity in childhood predisposes individuals to cardiovascular disease and increased risk of premature all-cause mortality. The aim of this study was to determine differences in LV morphology and function in obese and normal-weight adolescents. Furthermore, relationships between LV outcomes, cardiorespiratory fitness (CRF) and adiposity were explored. Methods LV morphology was assessed using magnetic resonance imaging (MRI) in 20 adolescents (11 normal-weight [BMI equivalent to 18 kg/m 2 –25 kg/m 2 ] and 9 obese [BMI equivalent to = 30 kg/m 2 ]); 13.3 ± 1.1 years, 45% female, Tanner puberty stage 3 [2–4] ) using magnetic resonance imaging (MRI). Global longitudinal strain (GLS), strain rate (SR) and traditional echocardiographic indices were used to assess LV function. CRF (peak oxygen consumption), percent body fat (dual-energy x-ray absorptiometry), abdominal adipose tissue (MRI), and blood biochemistry markers were also evaluated. Results Adolescents with obesity showed significantly poorer LV function compared to normal-weight adolescents (P  <  0.05) indicated by higher GLS (+ 6.29%) and SR in systole (+ 0.17 s - 1 ), and lower SR in early diastole (- 0.61 s - 1 ), and tissue Doppler velocities (S' - 2.7 cm/s; e' - 2.3 cm/s; A' - 1.1 cm/s). There were no group differences in LV morphology when indexed to fat free mass (P  >  0.05). Moderate to strong associations between myocardial contractility and relaxation, adiposity, arterial blood pressure and cardiorespiratory fitness were noted (r = 0.49–0.71, P  <  0.05). Conclusion Obesity in adolescence is associated with altered LV systolic and diastolic function. The notable relationship between LV function, CRF and adiposity highlights the potential utility of multidisciplinary lifestyle interventions to treat diminished LV function in this population. Clinical trial registration: NCT01991106.